Clinical profile of patients with abnormal uterine bleeding at a tertiary care hospital - Nair, Radha; M., Mallikarjuna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal uterine bleeding is a very common gynecological condition that affects all age groups. One third of patients attending gynaecology OPD present with complaints of abnormal uterine bleeding. Bleeding is said to be abnormal when the pattern is irregular, abnormal duration (>7 days), or menorrhagia or abnormal amount (>80 ml/menses). Methods: All patients in the perimenopausal age group (45±5 years) with symptoms of abnormal uterine bleeding presenting at department of OBG, Tertiary care centre during the study period were included in the study. Totally 50 study subjects were included in the study as this number of patients attended hospital during the study period. Results: The most common presenting symptom was pain abdomens (28%) followed by dysmenorrhea (16%), and back ache (2%). The most common bleeding pattern was menorrhagia (64%) followed by polymenorrhoea (28%), metrorrhagia (18%) and menometrorrhagia (8%). Conclusions: The entire bleeding pattern was more commonly associated with abnormal uterine bleeding.